MODEL PERKALIAN STICK, LINE AND FINGER MULTIPLICATION (UPAYA PENINGKATAN PEMAHAMAN MATERI KONSEP PERKALIAN PADA SISWA MADRASAI IBTIDAIYAH) - Mansur Syeban (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Pontianak, 2018)
The research is conducted because few students still could not understand the multiplication and division concept, especially on the lower class students (1, 2, and 3) in the elementary schools (SD/MI). Furthermore, this condition happened because mostly the homeroom teachers do not graduate from Homeroom Teacher Education (PGSD/PGMI), yet, Islamic Education alumni (PAI). Thus, the researcher would like to assess the application of Mathematics learning by Stick Multiplication Model, Finger and Line Multiplication to enhance the students’ understanding towards the multiplication concept in three Madrasah Ibtidaiyah Pontianak in 2017. This research, moreover, performs the positivism-quantitative method to test the hypothesis and do the experiment without compared group and pre-test. As a result of the research, the application of Mathematics learning using Stick Multiplication Model, Finger and Line Multiplication on students at second and third grade in the elementary school (SD/MI) factually could enhance their understanding on Multiplication Concept in the classroom. Besides, the results are varied based on students’ ability to absorb the study materials.